2018
DOI: 10.1186/s12906-018-2185-x
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activities and phenolic acid content of water and ethanolic extracts of the powdered formula of Houttuynia cordata Thunb. fermented broth and Phyllanthus emblica Linn. fruit

Abstract: BackgroundHouttuynia cordata Thunb. and Phyllanthus emblica Linn. are native plants with medicinal and nutritive significance in Asia. The present study was aimed at evaluating antiproliferative effects on human cancer cell lines and identifying the phenolic acid composition of water and ethanolic extracts of the powdered formula of H. cordata fermented broth and P. emblica fruit.MethodsAnticancer activity of the extracts was evaluated against HeLa, HT29, HCT116, MCF7 and Jurkat cells using an MTT assay and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…The differences were particularly expressed in the ferulic acid that was the most abundant phenolic acid in Puno extracts (78% of the total acids) but not identified in Titicaca extract. The results of other authors confirmed a significant cytotoxic effect of ferulic acid against colon cancer cells (Kumnerdkhonkaen et al, 2018; Saenglee, Jogloy, Patanothai, & Senawong, 2016). Furthermore, Zhang et al (2016) based on their research in vitro and in vivo models indicated that the ferulic acid has antitumor potential that could be used as a therapeutic agent against breast cancer.…”
Section: Resultssupporting
confidence: 54%
“…The differences were particularly expressed in the ferulic acid that was the most abundant phenolic acid in Puno extracts (78% of the total acids) but not identified in Titicaca extract. The results of other authors confirmed a significant cytotoxic effect of ferulic acid against colon cancer cells (Kumnerdkhonkaen et al, 2018; Saenglee, Jogloy, Patanothai, & Senawong, 2016). Furthermore, Zhang et al (2016) based on their research in vitro and in vivo models indicated that the ferulic acid has antitumor potential that could be used as a therapeutic agent against breast cancer.…”
Section: Resultssupporting
confidence: 54%
“…The researchers, therefore, studied the anti-cancer potential effect of both ethanolic plant extracts in further experiments. HCT was cytotoxic against many types of cancer cells, for example MCF-7 [9] and MDA-MB-231 [10]. Yet, there is still no report of the PR toxic effect on both types of breast cancer cells.…”
Section: Identification Of Phytochemical Compositions In H Cordata Amentioning
confidence: 99%
“…However, there were no significant differences between breast cancer cell viability at 48 and 72 h of incubation ( Figure 3). [9,11]. However, the anti-proliferation effect of P. ribesioides has not yet been studied.…”
Section: Identification Of Phytochemical Compositions In H Cordata Amentioning
confidence: 99%
See 1 more Smart Citation
“…Houttuynia cordata is a famous Chinese herb for clearing heat and eliminating toxins. [1] It also possesses many bioactivities including anticancer, [2] anti-inflammatory, [3] antibacterial, [4] antiviral, [5] and immunomodulatory functions. [6] In our study, we isolated the monomers of quercitrin and afzelin from Houttuynia cordata using bioactivity-guided fractionation and semipreparative liquid chromatography (SP-LC).…”
Section: Introductionmentioning
confidence: 99%